Internationalization, Digitalization, and COVID: A German Perspective - Rüland, Dorothea (International Higher Education, 2021)
Digitalization of higher education has been a pressing issue on the agenda for quite some time and for good reason. Higher education will look quite different after the COVID-19 pandemic: Digital change is not merely advancing technology, but organizational and systemic innovation that affects all areas of higher education and the educational system. The university of the future will, in all its aspects, be an international university, physically as well as virtually.